A Na/MnO2 Primary Cell Employing Poorly Crystalline MnO2. Issue 6 (26th February 2015) - Kishore, Brij; Venkatesh, G.; Munichandraiah, N.
Abstract : Presently Li/MnO2 is one of the widely used primary battery for a variety of applications. As the global resources for Na are plentiful in relation to those for Li, Na/MnO2 primary battery is expected to be an economical, viable alternate to Li/MnO2 system. But marginal inferior properties of Na/MnO2, which arise due to the differences in properties between Li and Na, are inevitable. In the present work, Na/MnO2 and Li/MnO2 laboratory scale primary cells in non-aqueous electrolytes are assembled and their electrochemical properties are studied in similar experimental conditions. The MnO2 used for these studies is prepared from KMnO4 and it is in amorphous state. The discharge behavior of Na/MnO2 cell is similar to that of Li/MnO2 cell, but with nominal voltage less by about 0.35 V, as expected. The specific capacity of amorphous MnO2 is 300 mAh g −1 in both Na/MnO2 and Li/MnO2 cells. On heating the as prepared amorphous MnO2 at temperature range 300–800°C, it converts to crystalline α-MnO2 . The capacity of crystalline MnO2 is significantly less than the amorphous MnO2 . The results suggest that Na/MnO2 is a viable, economical alternate to Li/MnO2 primary cell.